2020
DOI: 10.21203/rs.3.rs-33195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Two Embryo Culture Media, SOF and Commercial BO, on Pre- and Post-Implantation Development of Cloned Sannen Goat Embryos

Abstract: Background: The ingredients of embryo culture media developed by different companies are disclosed. Thus, it is impossible to determine which ingredients might be responsible for differences in pre-and post-implantation embryo development. To address this gap, we performed an experiment to compare two embryo culture media, namely, SOF and commercial BO, on pre- and post-implantation development of cloned Sannen goat embryos. Cumulus oocyte complexes derived from slaughterhouse ovaries were used for in vitro em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Non-physiological conditions in culture media and the addition of FBS have been shown to alter the expression of some genes, and there are also discrepancies in gene expression between embryos grown in laboratory conditions and those grown without serum. The expression of each gene is known to have a certain threshold, and an overabundance or dearth of expression may circumvent growth competence (30)(31)(32). Therefore, it is suggested that future research investigate the discrepancies in gene expression in embryos grown in culture media containing PL and FBS.…”
Section: Discussionmentioning
confidence: 99%
“…Non-physiological conditions in culture media and the addition of FBS have been shown to alter the expression of some genes, and there are also discrepancies in gene expression between embryos grown in laboratory conditions and those grown without serum. The expression of each gene is known to have a certain threshold, and an overabundance or dearth of expression may circumvent growth competence (30)(31)(32). Therefore, it is suggested that future research investigate the discrepancies in gene expression in embryos grown in culture media containing PL and FBS.…”
Section: Discussionmentioning
confidence: 99%
“…Zygotes were cultured at 38.5 °C, 5% CO 2, and 95% humidity in air for nine days. An inverted microscope (Leitz Fluovert FU; Leica Microsystems, Wetzlar, Germany) was used to examine a total of 370 culture zygotes (6 replicates) from both the two treat-ments for cleavage at 48 hours post-IVF and embryo development (blastocyst formation) at day 7 post IVF (Hajian et al, 2022).…”
Section: In Vitro Embryo Culture (Ivc)mentioning
confidence: 99%